Prevalence of partial edentulism according to Kennedy's classification based on age, gender, and arch - جركس, منار (Latakia University Journal -Medical Sciences Series, 2023)
Abstract: Knowledge about the most prevalent types of Kennedy classifications is of great value and will enlighten dental students, dental technicians, and practitioners regarding the treatment needs of their patients, ultimately leading to better treatment outcomes. Aim: This study aims to evaluate and compare the prevalence of various partial edentulism based on Kennedy’s classification in relation to arch, age, and gender of the patients. Methods: The study was conducted in patients attending an outpatient clinic at Al Andalus University for medical Sciences and Alwadi University. The survey was done in 359 patients based on age groups, arch (maxilla and mandible), and genders (male and female). The survey was done by doing visual examination for determining the prevalence of partial edentulism. The statistical analyses were performed with SPSS version 20.0 utilizing frequency and Pearson’s and Spearman’s correlation tests. Results: Kennedy’s Class III (44.1%) was the most prevalent pattern in both dental arches, followed by Class I (31%). Next was Class II (16.5%), while Class IV was the least prevalent (8.4%). Conclusion: Mandibular partial edentulism was found to be more common than maxillary partial edentulism. Kennedy Class III was the most noted classification in our patient population. Gender had no effect on the prevalence of various Kennedy’s classes, while age had a significant effect. As age increases, there is an increased tendency toward Class I and II.